Progression approach for image denoising - Bilal Charmouti; Ahmad Kadri Junoh; Mohd Yusoff Mashor; Najah Ghazali; Mahyun Ab Wahab; Wan Zuki Azman Wan Muhamad; Zainab Yahya; Abdesselam Beroual (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Removing noise from the image by retaining the details and features of this treated image remains a standing challenge for the researchers in this field. Therefore, this study is carried out to propose and implement a new denoising technique for removing impulse noise from the digital image, using a new way. This technique permits the narrowing of the gap between the original and the restored images, visually and quantitatively by adopting the mathematical concept ''arithmetic progression''. Through this paper, this concept is integrated into the image denoising, due to its ability in modelling the variation of pixels’ intensity in the image. The principle of the proposed denoising technique relies on the precision, where it keeps the uncorrupted pixels by using effective noise detection and converts the corrupted pixels by replacing them with other closest pixels from the original image at lower cost and with more simplicity.